Gender and leadership positions: understanding women's experiences and challenges in patriarchal societies in Northern Ghana - Adongo, Awinaba Amoah; Dapaah, Jonathan Mensah; Azumah, Francess Dufie (International journal of sociology and social policy, 2023)
PurposeWomen are rarely seen in positions of leadership in patriarchal societies, which is unsurprising. Following gender equity policies, few women have been able to break through the gender equity barrier and assume leadership positions in schools. Few research investigations have delved into the experiences and challenges that women encounter in positions of leadership in patriarchal societies in government schools in Northern Ghana. The study seeks to comprehend the experiences and challenges that women confront in positions of leadership in patriarchal societies in Northern Ghana.Design/methodology/approachThe study aimed to gain a better understanding of the experiences and challenges that women encounter in educational leadership roles in patriarchal societies in Northern Ghana. To achieve the study's objectives, a quantitative research approach and a social survey design were used, as well as descriptive and inferential statistics.FindingsThe findings of the study revealed that in patriarchal societies in Northern Ghana, women experience conventional gender roles that conflict with roles, cultural values, gender stereotyping, family responsibilities and cultural beliefs and perceptions of women and attitudes and low expectations of women's managerial skills discourage women from taking on leadership positions in men-dominated societies.Research limitations/implicationsThere is a need to shift the gender position and question the negative cultural convictions of cultural and patriarchal societies. Equal opportunities for men and women necessitate equal access to leadership positions. It proposes that in patriarchal societies, education and community stakeholder involvement in leadership training programmes for women be considered, as policy documents alone would not be sufficient to eradicate deeply embedded cultural social practices and dispel negative notions about women in leadership positions in men-dominated societies.Originality/valueThe study established that in patriarchal societies, women experienced conventional gender roles that conflict with roles, cultural values, gender stereotyping, family responsibilities, cultural vulnerability of women and the interplay between cultural expected roles and management goals influence women from taking on leadership positions.